Mode of loading in reflective and flexural fatigue cracking : a numeric evaluation - Sousa, Jorge B. (2000)
Consulpav international is working closely with the University of Minim in Portugal under a contract from the Rubber Pavements Association to develop a mechanistic procedure for overlay design that directly takes into account the mechanism of reflective cracking as well as classical flexural fatigue cracking. The problem of propcrly modeling the mechanism of renective cracking is paniclliarly pre\,alent in thin asphalt concrete overlays. To correctly model and predict asphalt fatigue mechanisms in overlays (both flexural and reflective cracking). it is necessary to utilize the correct mode of loading in laboratory tests. TIle mode of loading chosen should. as closely as possible. reflect the mode of loading which causes crack propagation in the field For cach of the possible distress mechanisms that cause cracking in pavements. such as thin or thick existing pavement sections. and thin or thick overlays. fatiguc characterization using any model must recognize that controlled stress. strain or "work"' (stress x strain) will inducc significantly different fatigue Ih'es in laboratory tests. As layer moduli are reduced by fatigue mechanisms. it is necessary to invcstigate which of these parameters (stress. strain or work) remains mostly constant in a field situation so that it can bc lIsed as an input control parameter in laboratory fatigue tests. This paper presents a numerical evaluation. through a finite element simulation. of mode of loading for scyeral types of nexible paYements and overlays placed on these pavements. Stress (load). strain (displacemcnt) and work (load x displacement) control modes are investigated.